Perancangan Aplikasi Media Pembejalaran Mata Pelajaran Jaringan Komputer Berbasis Android (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2023)
Telkom Sandhy Putra Medan Vocational School is an institution engaged in the field of education. During the current pandemic, all teaching and learning activities at Telkom Sandhy Putra Medan Vocational School are very limited by the government. The impact felt is very influential in all sectors, especially education. Students and teachers are only allowed to meet face to face for a few hours and not all students can enter the room, so that 1 class is divided into two waves. With this very limited time, of course not all of the material that will be delivered can be completed at the meeting, so usually the teacher takes the initiative by opening online classes so that material that is not discussed face-to-face can be completed. still delivered perfectly, especially in computer network subjects. However, there are still most students at Telkom Sandhy Putra Medan Vocational School who are lacking in capturing and understanding computer network lessons and most students do not understand computer network subjects because the learning process is conventional and results in students at Telkom Sandhy Putra Medan Vocational School not understanding network subjects computer and can result in students getting low grades. Also often found at Telkom Sandhy Putra Vocational High School Medan Lack of student interest in knowing computer network subjects because the learning process is still conventional and students have difficulty knowing and knowing computer network subjects at Telkom Sandhy Putra Vocational High School Medan